COMPARATIVE ANALYSIS OF MODELING SOFTWARE PACKAGES FOR ELECTRONIC CURCUITS - Давлет’янц, О.; Таран, Є.; Гальчун, О.; Лисенко, А. (Science-based technologies, 2010)
Article is devoted to analysis of the possibilities of modeling software packages and a better choice for modeling and study of electronic circuits and signals. The prospects for integration software in the learning process.